TYPES OF VERB PHRASE ERRORS MADE BY ENGLISH DEPARTMENT STUDENTS IN WRITING COMPARISON AND CONTRAST ESSAY AT STAIN BATUSANGKAR REGISTERED 2014/2015 ACADEMIC YEAR - HENDRA PUTRA (Jurnal Sinar Edukasi, 2020)
This research is conducted because it is based on the phenomenon of the many types of errors that occur in students' essays or writings. The purpose of this research is to find and analyze the types of errors contained in the essays of fourth semester students at STAIN Batusangkar and what are the causes of these errors. This research is classified in a qualitative descriptive research. The data in this research is test errors found in student essays. Data is collected through comparisons and contrast essay writing exams and interviews. The data source in this research is English language education students in the fourth semester of 2014/2015 academic year. The findings from this research indicate that the most common types of errors in writing comparisons and contrasts are matching between the subject of a sentence and the verb. And the causes of these types of errors are caused by three factors. The first factor is interlingua transfer. They wrote what they thought is immediately transferred to English. The second factor is intralingua transfer, in this factor many students write English not according to their sentence structure or sentence structure. It can be concluded that the types of errors in writing essays made by English language education students mostly occur in verb phrases. In one sentence can be found that several types of errors made by the student.